Effect of freezing temperature on impact bending strength and shore-D hardness of some wood species - Osman Emre Özkan (BioResources, 2022)
Wood is exposed to variable environmental conditions during its use. Low temperature is one of the most important environmental factors affecting the behavior of wood in use. Contrary to other mechanical properties, there are not enough studies on how the impact bending strength is affected during freezing of wood. This study evaluated the effect of various freezing temperatures (-20, -40, -78.5, and -196 °C) on the impact bending strengths of beech (Fagus orientalis Lipsky), Scotch pine (Pinus sylvestris L.), fir (Abies nordmanniana subsp. bornmulleriana), and spruce (Picea orientalis L.) wood in comparison with non-frozen wood (+20 °C). During the freezing, the impact bending strength generally increased in softwood species but decreased in hardwood. The highest drop in impact bending strength value of -30.6% was found at -196 °C for beech wood. For this reason, precautions should be taken when using beech wood at ultra-low temperatures, due to substantial decreases in impact bending strength values. The good impact bending strength properties of the softwood while frozen allows application in low temperature environments.
Keywords: fir; shock resistance; low temperature; scotch pine; beech; TP248.13-248.65; spruce; Biotechnology; 13. Climate action